Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Saham Pada Perusahaan Non-Keuangan Di Bursa Efek Indonesia Tahun Periode 2012-2014 - Rizkiawan, Ilham Karin, Drs. Sujadi, M.M (2016)
This research aims to test the influence of variables size, underwriter, leverage, return on equity (ROE) collectively and individually towards underpricing at non-financial companies listed on the Indonesia Stock Exchange. This research is associative research and the type of data is secondary. Those are obtained from data pulished by Indonesia Stock Exchange which has audited for research period. Method of data collection used study literature. The analysis methods used is descriptive statistics and multiple linear egression. The population of this research is a non-financial company in Indonesia Stock Exchange that do an IPO (Initial Public Offering) in the period 2012-2014, which amounts to 60 companies. The sample of this research are 42 companies, which was done by using purposive sampling method.The results of this research show that simultaneously, size, underwriter, leverage, and return on equity (ROE) are jointly contributing significantly to the underpricing. Partially, the size, underwriter and return on equity (ROE) has a negative and significant effect to underpricing, while leverage have a significant and positive effect to underpricing at non-financial companies doing Initial Public Offering (IPO) on the Indonesia Stock Exchange.